Identifying Disordered Intermediates in the Reaction of Cu3– x P and Dibenzyl Diselenide to form Cu3PSe4 Nanoparticles - Luke T. MacHale; Lauren Borgia; Monika J. Perez; Nathan A. Neisius; Ifeoluwa P. Oyekunle; Mirella K. Villani; Bright O. Ogbolu; Erin R. Snyder; Sadegh Yazdi; Autumn N. Peters; Yan-Yan Hu; James R. Neilson; et al. (Journal of the American Chemical Society, 2026)
Abstract Developing a detailed understanding of ternary nanoparticle (TNP) formation is essential for their optimized rational synthesis and development of synthetic routes for new TNPs. Herein, we explore the reaction of Cu3–xP and dibenzyl diselenide (Bn2Se2) to form colloidal Cu3PSe4 TNPs. Temperature-resolved X-ray scattering (XRD and PDF), electron microscopy (TEM and STEM), and spectroscopy (EDS, EELS, XPS, and MAS NMR) reveal that Cu3–xP reacts by surface coordination of Se leading to fragmentation followed by rearrangement to Cu–Se binary phases, during which all obvious crystalline P-containing phases disappear via XRD. However, partially oxidized P in solid phases was observed using STEM-EDS and XPS, in which P is found to preform P–Se bonds prior to Cu3PSe4 formation. Using a combination of 31P MAS NMR and PDF analysis obtained from synchrotron total scattering data, P–Se bonds in [PSe4]3– tetrahedral building blocks were identified within intermediate Cu–Se phases containing P cation substitution (PCu), denoted (Cu,P)–Se, that assemble into Cu3PSe4. We hypothesize that these intermediate compounds with their substoichiometric, vacancy-rich structures and significant Cu disorder are important for accessing Cu3PSe4─offering a new insight into complex TNP syntheses. We summarize our findings by writing plausible pseudoelementary steps (PESteps) in which the Cu3–xP precursor converts to smaller fragments of Cu–Se phases containing P en route to the final Cu3PSe4 product. Additional interesting aspects of this system include the use of Bn2Se2 as a readily monitorable probe for the reaction and the Se–P bond formation that facilitates Cu–P bond cleavage in an overall 8-electron redox reaction involving P3– and 4 Se0. The results obtained lay the groundwork for future mechanistic investigations, notably kinetics studies working from the PESteps aimed ultimately at the rational design and synthesis of complex ternary pnictogen chalcogenide nanoparticles.